The Effectiveness of Chain Pumpkin on Improving Breast Milk Production and Increasing Baby's Weight - Gusrida Umairo; Titin Kartini; Yessi Hastuti; Siti Rohmah; Siti Nurlaela Jamilah (Postgraduate, University of Mataram, 2024)
A Breast milk is the best nutrition for babies because it is easy to digest and contains the nutrients needed for growth and immunity. This research aims to determine the effectiveness of chayote in smoothing breast milk production and increasing baby weight. This research uses a two group pretest-posttest design method without a control group, with measurements taken before and after treatment. The independent variable is the method of consuming chayote, while the dependent variable is the smooth production of breast milk and the increase in baby weight. This research produced information that the P-Value value obtained for increasing the smoothness of breast milk production (0.000 for boiled chayote and 0.001 for fried chayote) showed a significant difference. The P-Value value obtained for increasing baby weight (0.000 for boiled chayote and 0.003 for fried chayote) shows a significant difference. Based on these data findings, breastfeeding mothers are expected to consume chayote, both boiled and fried, as part of their diet to support smooth breast milk production and baby growth.